Convicts: Criminal Group Members in the Opinions of Prison Service Officers (Archives of Criminology, 2008)
The goal of this text is to examine the group of convicts who are members of criminal groups as unique and distinguishable from other groups of inmates, from the point of view of Prison Service officers. Despite the fact that members of criminal groups in detention centres and penitentiaries constitute only 3.7% of the total prison population, they are perceived as special due to the fact that they have been convicted of crimes with a high degree of social harm. The author, in supporting the thesis presented in the article, draws attention first of all to the long list of acts committed by these convicts, such as: human trafficking, organisation of illegal migration, forgery of money and documents, illegal production of weapons, smuggling of narcotics, economic fraud, organisation of illegal prostitution, illegal gambling, robbery, or even contract killings. Next, relying on the content of Article 90 of the Penal Code, Grażyna B. Szczygieł describes special conditions of serving a sentence, such as closed cells, supervised movement around the prison, employment under escort, or the right to two visits per month. The text also outlines other provisions of the code. As the author rightly points out, although the law clearly states that the conditions of imprisonment for persons convicted of involvement in a criminal group are insufficient and should be tightened in comparison with the conditions of imprisonment in a detention facility, it did not specify them in detail in the cited provisions. Additional conditions for the imprisonment of the above-mentioned prisoners is contained in Art. 88b of the Penal Code, including round-the-clock closing of cells and more frequent inspections of prisoners by psychologists and wardens who work with this group of prisoners. The author then presents the findings of a research project entitledLegal and organisational-technical solutions in combating organised crime with particular reference to the issue of litigation evidence and the institution of a state witness,2000–2006. Among the problems raised in the study, there were issues of assessing the changes that resulted from the appearance of inmates who were members of criminal groups in prisons. The empirical material was comprised of the statements of 705 Prison Service officers, including 210 educators, 495 wardens, and 43 psychologists, who had direct contact with the convicts under study. The article discusses the following characteristics among convicted members of criminal groups: better material situation, higher intelligence level, more intensive care for tidiness in one’s cell, personal appearance and physical strength, increased entitlement, better orientation in one’s rights, or close contact with one’s family. In conclusion, the author draws particular attention to the danger of other convicts’material dependence on members of criminal groups. This situation can lead to members of criminal groups forcing the convicts benefiting from their material support to engage in behaviours that threaten the safety of Prison Service officers.